Apparent competition drives community-wide parasitism rates and changes in host abundance across ecosystem boundaries - Frost, Carol M.; Peralta, Guadalupe; Rand, Tatyana A.; Didham, Raphael K.; Varsani, Arvind; Tylianakis, Jason M. (Nature communications, 2016)
Species have strong indirect effects on others, and predicting these effects is a central challenge in ecology. Prey species sharing an enemy (predator or parasitoid) can be linked by apparent competition, but it is unknown whether this process is strong enough to be a community-wide structuring mechanism that could be used to predict future states of diverse food webs. Whether species abundances are spatially coupled by enemy movement across different habitats is also untested. Here, using a field experiment, we show that predicted apparent competitive effects between species, mediated via shared parasitoids, can significantly explain future parasitism rates and herbivore abundances. These predictions are successful even across edges between natural and managed forests, following experimental reduction of herbivore densities by aerial spraying of insecticide over 20 hectares. This result shows that trophic indirect effects propagate across networks and habitats in important, predictable ways, with implications for landscape planning, invasion biology and biological control. Species sharing a common enemy such as a parasitoid or predator can indirectly affect one another. Here, Frost et al . use quantitative food-web data from communities of caterpillar hosts to show experimentally that apparent competition is important in predicting food-web structure across habitats.